Significantly enhanced thermal conductivity in polyvinyl alcohol composites enabled by dopamine modified graphene nanoplatelets. (February 2019) - Liu, Yingchun; Wu, Kun; Luo, Fubin; Lu, Maoping; Xiao, Fei; Du, Xiangxiang; Zhang, Shiheng; Liang, Liyan; Lu, Mangeng
Abstract: Inspired by mussels, dopamine was used to modify graphene nanoplatelets (GnPs). The GnPs@polydopamine (GnPs@PDA) fillers were prepared as fillers and polyvinyl alcohol (PVA) composites were fabricated via casting method. Composites exhibited excellent flexibility and tensile strength increased by 12% at 2.5 wt.% GnPs@PDA loading. The thermal conductivity(λ) of the composites reached 13.4 W m −1 K −1 with loading 10 wt.% GnPs@PDA, which was increased by 4300% compared that of PVA. FTIR results of PVA/PDA films showed that PVA OH and CO stretching vibration have shifted, which proved that hydrogen bonds were formed between GnPs@PDA and PVA. The crystallinity of PVA decreased in the composites indicated that hydrogen bonds were formed between the PVA matrix and the PDA. In addition, the interface compatibility between the GnPs@PDA and PVA matrix was enhanced. Thus, an effective thermal conductive network was formed through hydrogen bonds in composites. These results lead a high λ for films.